2011
DOI: 10.1159/000326623
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Human Stem Cells for Clinical Application: A Review

Abstract: Stem cells have been used in a clinical setting for many years. Haematopoietic stem cells have been used for the treatment of both haematological and non-haematological disease; while more recently mesenchymal stem cells derived from bone marrow have been the subject of both laboratory and early clinical studies. Whilst these cells show both multipotency and expansion potential, they nonetheless do not form stable cell lines in culture which is likely to limit the breadth of their application in the field of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
209
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(212 citation statements)
references
References 188 publications
(179 reference statements)
1
209
0
2
Order By: Relevance
“…Using mixtures of cryoprotectants helps to reduce the intrinsic toxicity of each, and the method published by Reubinoff et al utilized 20% DMSO, 20% ethylene glycol and 0.5 mol/l sucrose (Reubinoff et al, 2001). However, no studies have been reported so far to determine the permeability of the cells (or colony fragments) to either cryoprotectant, or the intrinsic toxicity of these components to hESCs (Hunt, 2011).…”
Section: Vitrification and Optimizations Of The Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Using mixtures of cryoprotectants helps to reduce the intrinsic toxicity of each, and the method published by Reubinoff et al utilized 20% DMSO, 20% ethylene glycol and 0.5 mol/l sucrose (Reubinoff et al, 2001). However, no studies have been reported so far to determine the permeability of the cells (or colony fragments) to either cryoprotectant, or the intrinsic toxicity of these components to hESCs (Hunt, 2011).…”
Section: Vitrification and Optimizations Of The Techniquementioning
confidence: 99%
“…In contrast, vitrification overcomes the problems associated with ice crystallization in a different manner. Here cryoprotectants are used in high concentrations preventing ice formation entirely (Baust et al, 2009;Hunt, 2011).…”
Section: Usage Of Different Cryoprotective Agents and Vehiclesmentioning
confidence: 99%
“…Whilst conventional slow freezing generally yields over 90% viability post-thaw (Kleeberger et al 1999;Kotobuki et al 2005), for certain cell types such as human embryonic stem cells (hESC) grown as colonies, poor survival has been reported (Li et al 2010;Xu et al 2010). Vitrification is an alternative approach for storage of hESC (Li et al 2010), yet is disadvantaged due to higher concentrations of cryoprotective agents (CPAs), smaller storage volumes (typically 1-20µl per cryostraw) (Unger et al 2008;Coopman 2011;Hunt 2011) and the risk of contamination from open cryostraws (Mirabet et al 2012). Diminished functionality of cryopreserved human hepatocytes has also been documented; with cells losing their adherence capabilities and exhibiting an altered metabolic profile post-thaw (Terry et al 2006).…”
Section: The Importance Of a Short-term Cell Preservation Platformmentioning
confidence: 99%
“…Osmotic imbalances can injure cells and programmed cell death may be induced upon thawing (Mathew et al 2002). Further to this, dimethyl sulfoxide (DMSO), the most frequently used CPA, is considered toxic to cells at ambient temperatures (Hunt 2011) and may induce cell differentiation (Santos et al 2003). Patients infused with DMSO-preserved cells can also experience adverse reactions (Cox et al 2012).…”
Section: The Importance Of a Short-term Cell Preservation Platformmentioning
confidence: 99%
“…It is well known that DMSO is potentially cytotoxic, and transplantation of DMSO-preserved human BM cells has been shown to cause severe adverse reactions. 20 Moreover, the use of human serum albumin, cerebrospinal fluid, fetal bovine serum, and bovine serum albumin as cryoprotectants is also problematic, due to the risk of contamination with human or animal viruses and the potential of infection with prions and other unidentified pathogens. 21 In addition, these are potentially dangerous due to the possible induction of an allergic response.…”
Section: Cell Characterization Considerations For Fresh Cellsmentioning
confidence: 99%